Ketahanan Pelaku Usaha Dalam Memacu Peningkatan Perilaku Kreatif Masa Pasca Pandemi Covid 19 - Edi Sugiono; Santi Retno Sari; Dita Nurul Aini Mustika Dewi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study carries a model by proving that creativity is influenced by behavioral resilience through the development of business actors moderated by the creative self-efficacy of business actors. A total of 107 small, micro, and medium enterprises spread across the island of Java were the samples for this study. Sampling technique with snowball sampling. Analysis technique by testing mediation moderation with ProcessV3.5. The results support the six hypotheses and prove the model that resilience influences creative behavior through growth which is moderated by the creative self-efficacy of business actors. Promoting the creative economy requires actors who are also creative. The creation and improvement of the creative behavior of business actors is necessary to create and increase their resilience, development and self-efficacy.